Prevalence of Oedematous Malnutrition in Early Infancy - Begum, Ayesha; Sharma, Jhulan Das; Azad, Abul Kalam; Mahmud, Nazir Uddin; Ahmad, Mainuddin (Journal of Chittagong Medical College Teachers’ Association, 2011)
Key words: malnutrition; infancy; skin changes DOI: 10.3329/jcmcta.v21i1.7679 Journal of Chittagong Medical College Teachers' Association 2010: 21(1):50-55